Molecular Fish Sexing on Taisho Sanshoku Koi (Cyprinus carpio) Based on ArS.9-15 Gene Amplification using PCR Method - Novindasari, Balqis Bahiya Milan; Nurrahmi, Isti Ananda; Andrian, Krisna Noli; Haryanto, Aris (Universitas Airlangga, 2024)
Taisho Sanshoku is a variant of Koi fish (Cyprinus carpio) that has high demand due to its high economic value and relatively expensive price. This study aimed to determine the sex of the Taisho Sanshoku Koi fish by molecular sexing using the PCR method to amplify the ArS.9-15 gene. This study was initiated by rearing a 4–6 month-old of 10 Taisho Sanshoku Koi fish in a fish tank with a filter and oxygen aeration. The fish were fed with fish pellets for 1–3 days. The Koi fishes were then anesthetized using Koi anesthesia containing β-hydroxyethyl phenyl ether. Each fish's peripheral blood was collected as much as 0.5 mL per fish and then stored in tubes containing Ca-EDTA anticoagulant. The genomic DNA was extracted from peripheral blood samples and used as a template DNA for PCR amplification targeting ArS.9-15 gene. Agarose with 1.5% concentration and CybrSafe staining was used in electrophoresis for visualization of the PCR results then visualized in a dark chamber using a UV transilluminator. The Taisho Sanshoku Koi fish's sex was determined using descriptive analysis based on the electrophoresis results. According to the PCR results, the female Taisho Sanshoku Koi fish only produced one 800 bp DNA band, whereas the male fish produced two 800 bp and 1,100 bp DNA bands. The outcome of molecular fish sexing of the 10 Taisho Sanshoku Koi fish reported that 60% were male and 40% were female.